Stability of superposed fluids through magnetic field with suspended particles of different permeability saturated through porous layer - Singh, Mahinder (Zielona Góra: Uniwersytet Zielonogórski)
The instability of plane interface between two superposed Rivlin-Ericksen elastico-viscous fluids saturated through a porous medium has been studied to include the suspended (dust) particles effect. Following the linearized stability theory and normal mode analysis the dispersion relation is obtained. For stationary convection, the Rivlin-Ericksen elastico-viscous fluid behaves like Newtonian fluids.
Keywords: porous medium; suspended particles; Rivlin-Ericksen fluid and magnetic field